Hubungan Manusia dan Tuhan Dalam Puisi Klasik Religi Karya Taufiq Ismail, Amir Hamzah, dan Emha Ainun Najib - Azzahra, Safira; Haryanti, Novi Diah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this study is to find out and to make an analogy of the poet's visualization of three different poems with religious genres. The themes raised in the poetry are also different, there are also poems with the theme of people's struggle, the theme of human greed for nature, as well as religious themes whose meaning is often revealed implicitly in poetry. This study uses qualitative research using a comparative literature approach. The data taken in this study are the text of the poem "Sajadah Panjang" by Taufiq Ismail, the poem "Insaf" by Amir Hamzah, and the poem "When You Pray" by Emha Ainun Najib. By using data analysis techniques, namely by way of content analysis techniques. From the results of this study it was found regarding the depiction of Taufiq Ismail, Amir Hamzah, and Emha Ainun Najib on the relationship between humans and God which is built through poetry. The three poems that have been reviewed show some similarities that can be seen upon further examination.